Az európai társadalmi változások néhány új vonása (1960-2010) : megfontolások a délkelet-európai kutatások programalkotói számára - Glatz, Ferenc (Közép-Európai Közlemények, 2013)
What are the most important social changes now occuring on the European continent, and in the European Union? Changes that we, living in the Southern-Eastern region have to take into consideration, being either regionalists, geographers, or facilitators of science. I suggest some considerations to the editors of the journal now publishing its 20th issue, hoping that my remarks will be useful when deciding on the topics of further issues and conferences.